Implementasi Sistem Informasi Geografis untuk Pemetaan Sebaran Jumlah Penduduk di Kota Cimahi - Dani Hamdani; R.A.E Virgana T Saptanji (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2020)
The Cimahi Regional RPJP 2005-2025 states that population growth and its distribution have become strategic issues and need to be addressed in a gradual and continuous manner, therefore monitoring population distribution is something that must be carried out sustainably. The software development method used is the Rational Unified Process (RUP) method. RUP uses the object-oriented concept, with activities that focus on developing models using the Unified Model Language (UML). This research aims to build a geographic information system that displays a mapping of population distribution in Cimahi City. The data was obtained from the Cimahi City Central Statistics Agency publication. This system was built using QGIS to build maps, PostgreSQL for database management and PHP programming language to display maps to web pages. The final conclusion of this study found that the geographic information system that was built can show information about the distribution of residents of Cimahi City well so that the government can determine more appropriate policies.